PELATIHAN DAN KOMPETISI GOARA-GOARA TINGKAT INTERNASIONAL DI UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA TAHUN 2026 - Slamet Santoso; Shodiq Hutomono; Teguh Andibowo; Teguh Santosa; Erik Teguh Prakoso; Faridha Isnaini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tunas Pembangunan Surakarta, 2026)
Technological advancements should be leveraged to revitalize traditional games, making them more engaging and ensuring their preservation for future generations. However, technology can also negatively impact traditional games, as children today often no longer play them. Driven by a passion for culture, academics have felt compelled to preserve local wisdom and traditional games. Efforts to conserve and reintroduce these nearly extinct traditional games have taken the form of international-level training sessions and competitions for